2021
DOI: 10.3389/fpsyg.2021.777472
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Responses Toward a New Research Policy Among Academics in a Chinese University

Abstract: Teacher emotion has received prominent attention in the field of education as they are closely related to teacher identity and teachers’ well-being. While many previous studies have taken teachers’ emotions in teaching as their research focuses, this study investigated university English as a foreign language (EFL) teacher-researchers’ emotions and emotion regulation strategies in research in the context of a new research policy. One-on-one semi-structured interviews were conducted with seven EFL teacher-resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…According to Tran et al's (2017) study on English language teachers in Vietnam, while few academics expressed support and enthusiasm for a new institutional research policy, the majority uttered pressure and complaints about the overemphasis on research excellence in policy documents. Similarly, in Lu and Zhang's (2021) study on the emotional responses of a group of EFL academics to China's new research policy breaking the ''Five-Only'' (China's new national research policy that seeks to replace the old quantitative evaluation system's emphasis on academics' papers, educational credentials, professional titles, research awards, and honorary titles [Luo, 2020]), the majority expressed dissatisfaction with the changes brought about by the new policy, whereas only a few expressed joy and welcomed the changes. Evidence from various contexts indicates that emotion is an unavoidable part of change, and negative emotions seem to be the dominant responses among EFL academics toward the research emphasis at the socioinstitutional level, particularly in the reform period.…”
Section: Efl Teachers' Emotions In Research Practicementioning
confidence: 91%
See 1 more Smart Citation
“…According to Tran et al's (2017) study on English language teachers in Vietnam, while few academics expressed support and enthusiasm for a new institutional research policy, the majority uttered pressure and complaints about the overemphasis on research excellence in policy documents. Similarly, in Lu and Zhang's (2021) study on the emotional responses of a group of EFL academics to China's new research policy breaking the ''Five-Only'' (China's new national research policy that seeks to replace the old quantitative evaluation system's emphasis on academics' papers, educational credentials, professional titles, research awards, and honorary titles [Luo, 2020]), the majority expressed dissatisfaction with the changes brought about by the new policy, whereas only a few expressed joy and welcomed the changes. Evidence from various contexts indicates that emotion is an unavoidable part of change, and negative emotions seem to be the dominant responses among EFL academics toward the research emphasis at the socioinstitutional level, particularly in the reform period.…”
Section: Efl Teachers' Emotions In Research Practicementioning
confidence: 91%
“…Yang et al (2022) found that while research performers and followers were afflicted by many negative emotions such as unhappiness and helplessness, accommodators and integrators showed a mixture of both positive and negative emotions as they responded to the culture of performativity. In addition, scholars noticed that EFL teachers demonstrated a wide range of emotional responses toward changes in institutional research policies (Lu & Zhang, 2021; Tran et al, 2017). According to Tran et al’s (2017) study on English language teachers in Vietnam, while few academics expressed support and enthusiasm for a new institutional research policy, the majority uttered pressure and complaints about the overemphasis on research excellence in policy documents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mediated by their effects on such behaviours as academic writing, the influence of publishing policies even reaches the affective aspects of researchers' professional experience. For instance, Lu and Zhang's (2021) study reveals that university researchers experienced wide-ranging and diverse emotions at various levels of research, and displayed different attitudes towards the research policy at their university. In short, publishing policies influence university researchers' publishing engagement in both behavioural and cognitive terms.…”
Section: Publishing As a Field Of Actionsmentioning
confidence: 99%
“…On the other hand, students, as the primary stakeholders that teachers face in their daily teaching, are affected not only by teacher emotions in the classroom ( Frenzel et al, 2009a ; Becker et al, 2014 ) but also have a far-reaching impact on their learning, including academic achievement ( Kunter et al, 2011 ), motivation ( Kunter et al, 2013 ), and so on. At the macro level, teachers’ emotions can influence the implementation of various educational reforms ( Hargreaves, 1998 ; Lu and Zhang, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research has revealed that teacher emotions differ across disciplines and key stages in school education (such as primary, middle, high school, and university; Frenzel et al, 2009b , 2015 ). Among the available studies, research on language teachers dominates the discipline research ( Golombek and Doran, 2014 ; Chu et al, 2021 ; Heydarnejad et al, 2021 ; Sun and Yang, 2021 ; Liu et al, 2022 ), and the research on key stages is mainly focused on primary school and university teachers ( Gu, 2016 ; Chen, 2017 , 2019 ; Lu and Zhang, 2021 ), whereas high school mathematics teacher emotions have received less attention ( Martínez-Sierra et al, 2019 ; Jiang et al, 2021 ). However, the uniqueness of high school mathematics teachers in terms of their key stages and disciplines, particularly in China, where high school mathematics teachers are also under the pressure of Gaokao (the National College Entrance Examinations; Jiang et al, 2022 ), makes their professional background and emotional development unique and deserving of more in-depth and focused research.…”
Section: Introductionmentioning
confidence: 99%